Paraspinal muscle oxygenation and mechanical efficiency are reduced in individuals with chronic low back pain - Agathe Anthierens; André Thevenon; Nicolas Olivier; Patrick Mucci (Scientific Reports, 2024)
Abstract This study aimed to compare the systemic and local metabolic responses during a 5-min trunk extension exercise in individuals with chronic low back pain (CLBP) and in healthy individuals. Thirteen active participants with CLBP paired with 13 healthy participants performed a standardised 5-min trunk extension exercise on an isokinetic dynamometer set in continuous passive motion mode. During exercise, we used near-infrared spectroscopy to measure tissue oxygenation (TOI) and total haemoglobin-myoglobin (THb). We used a gas exchange analyser to measure breath-by-breath oxygen consumption (V̇O2) and carbon dioxide produced (V̇CO2). We also calculated mechanical efficiency. We assessed the intensity of low back pain sensation before and after exercise by using a visual analogue scale. In participants with CLBP, low back pain increased following exercise (+ 1.5 units; p < 0.001) and THb decreased during exercise (− 4.0 units; p = 0.043). Paraspinal muscle oxygenation (65.0 and 71.0%, respectively; p = 0.009) and mechanical efficiency (4.7 and 5.3%, respectively; p = 0.034) were both lower in participants with CLBP compared with healthy participants. The increase in pain sensation was related to the decrease in tissue oxygenation (R2 = − 0.420; p = 0.036). Decreases in total haemoglobin-myoglobin and mechanical efficiency could involve fatigability in exercise-soliciting paraspinal muscles and, therefore, exacerbate inabilities in daily life. Given the positive correlation between tissue oxygenation and exercise-induced pain exacerbation, muscle oxygenation may be related to persisting and crippling low back pain.